Uji Beberapa Dosis Tepung Daun Gamal (Gliricididia sepium Jacq.) Terhadap Sitophilus oryzae L. Pada Beras Di Penyimpanan - Rustam, Rusli; Sutikno, Agus; Laila, Jamiatul (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2017)
Rice is one of serealea comodity that susceptible with pest storage. One of the pest that often attack the rice in storage is Sitophilus oryzae L. The alternative for control S. oryzae L. as fumigant which enviromentally sound is Gliricidia sepium Jacq. as organic insecticide. This research aims to get the best dose G. sepium Jacq. leaf powder to control S. oryzae L. pest in rice storage. This research conducted at Laboratory of Plant Pest, Faculty of Agriculture, University of Riau, Pekan baru from Mei until Juni 2016. This research arranged experimentally by using Completely Randomized Design consisting of 5 treatments and 4 replications. The treatment consist of 5 dose levels were 0 g/100 g rice, 2 g/100 g rice, 4 g/100 g rice, 6 g/100 g rice and 8 g/100 g rice. The result showed that giving of G. sepium Jacq. leaf powder with dose 8 g/100 g rice causes time of death beginningS. oryzae L. during 31.50 hours after application, lethal time 50 during 282.8 hours after application, total mortality was 70%, amount of generation was 9,75 beetles and decrease of seed weight’s rice was 1.08%.